2017
DOI: 10.1523/eneuro.0182-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Prestimulus EEG Power Predicts Conscious Awareness But Not Objective Visual Performance

Abstract: Prestimulus oscillatory neural activity has been linked to perceptual outcomes during performance of psychophysical detection and discrimination tasks. Specifically, the power and phase of low frequency oscillations have been found to predict whether an upcoming weak visual target will be detected or not. However, the mechanisms by which baseline oscillatory activity influences perception remain unclear. Recent studies suggest that the frequently reported negative relationship between α power and stimulus dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
206
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 186 publications
(242 citation statements)
references
References 77 publications
25
206
11
Order By: Relevance
“…This finding convincingly ties cortical excitability in our paradigm to a strategically applied criterion shift, as opposed to a change in detection sensitivity. Convergently, other studies also report a link between prestimulus low-frequency EEG activity and subjective perception, but not objective task performance 32,33 .…”
Section: Discussionmentioning
confidence: 93%
“…This finding convincingly ties cortical excitability in our paradigm to a strategically applied criterion shift, as opposed to a change in detection sensitivity. Convergently, other studies also report a link between prestimulus low-frequency EEG activity and subjective perception, but not objective task performance 32,33 .…”
Section: Discussionmentioning
confidence: 93%
“…Beta-band power in particular is associated with feedback signals (Bastos et al, 2015), stronger attention and top-down control (Buschman and Miller, 2007;Salazar et al, 2012), and the prioritization of the current brain states over new inputs (Spitzer and Haegens, 2017). In support to this view, stronger low frequency (<30 Hz) oscillations attenuate early evoked sensory responses (Iemi et al, 2019), increase the criterion of perceptual detection (resulting in fewer detections) by modulating baseline excitability (Limbach and Corballis, 2016;Benwell et al, 2017;Craddock et al, 2017;Iemi et al, 2017) and degrade performance in perceptual decisions (Haegens et al, 2011).…”
Section: Discussion (1500)mentioning
confidence: 97%
“…Recent studies have suggested that pre-stimulus alpha activity may reflect the criterion used to commit a specific response and may hence reflect a perceptual or decisional bias (Limbach & Corballis, 2016;Iemi, Chaumon, Crouzet, & Busch, 2017;Craddock, Poliakoff, El-deredy, Klepousniotou, & Lloyd, 2017;Iemi & Busch, 2018;Rohe, Ehlis, & Noppeney, 2019). Along such a role in perceptual decision making, alpha activity was shown to correlate with subjective awareness (Benwell, et al, 2017;Lange, Oostenveld, & Fries, 2013;Gulbinaite, İlhan, & VanRullen, 2017) and decision confidence (Samaha, Iemi, & Postle, 2017;Wöstmann, Waschke, & Obleser, 2018). Still, it remains unclear whether pre-stimulus activity indeed reflects an individual's intrinsic bias, or reflects processes that facilitate veridical sensory encoding, as previous work did not unambiguously quantify the relation of spontaneous brain activity to idiosyncratic and temporary biases.…”
Section: Introductionmentioning
confidence: 99%